EFFECTIVENESS OF COMPLEX HOMEO-PATHIC PREPARATION AND PHYTOCON-CENTRATE IN PATIENTS SUFFERING FROM CHRONIC CHOLECYSTITIS - Павловський, С.А. (World of Medicine and Biology, 2015)
As a result of the clinical studies, patients diagnosed with chronic cholecystitis in most cases show signs of autonomic dysfunction, emotional stress, anxiety and hypochondria disorders noted various complaints of pain in the right hypochondrium without exacerbation of chronic cholecystitis. This is symptomatic of underlying disease does not always bring the desired effect and more often than not reduces complaints and normalization of the patient. In this regard, we have decided to evaluate the effectiveness and feasibility of complex homeopathic preparation “Nervoheel” and phytoconcentrate “Nevryn” in patients with chronic cholecystitis as without comorbidity and associated with somatoform dysfunction of the autonomic nervous system against the background of disturbed circadian rhythm. After analyzing the results of this study, we concluded that the appointment of these drugs significantly affects the symptoms of a chronic cholecystitis and comorbidity, reducing the patient’s complaints on disorders of the gastrointestinal tract and autonomic nervous system.
Keywords: chronic cholecystitis; vegetative disorders; “Nervoheel”; “Nevryn”